BOOSTING CORPORATE RESPONSIBILITY THROUGH ECO-MARKETING STRATEGIES IN RETAIL: ALIGNING WITH GLOBAL MARKET TRENDS (Marketing Journal, 2024)
The retail industry is increasingly recognizing the critical role of sustainability and corporate responsibility in achieving business success within the global marketplace. This article explores the integration of eco-marketing strategies as a means to enhance corporate responsibility and align with prevailing global market trends that favor environmentally conscious practices. Through a comprehensive literature review, the study examines key eco-marketing components such as sustainable product sourcing, energy efficiency, waste reduction, eco-friendly packaging, and green supply chain management. Additionally, the research highlights the importance of consumer education, digital marketing, loyalty programs, and strategic partnerships in fostering sustainable consumer behavior and strengthening brand loyalty.